Design reality gap issues within an ICT4D project: an assessment of Ji gawa State Community Computer Center - Kanya, Rislana Abdulazeez; Good, Alice (2013)
This paper evaluates the Jigawa State Government Community Computer ce ntre project using the design reality gap framework. The purpose of th is was to analyse the shortfall between design expectations and implem entation realities, in order to find out the current situation of the project. Furthermore to analyse whether it would meet the key stakehol der’s expectation. The Majority of Government ICT Projects is classifi ed as either failure or partial failure. Our research will underpin a case study of Jigawa State Community Computer centre project. To suppo rt our argument we conducted a qualitative case study in which we cond ucted two interviews, and a survey to find out the current status of t he project. Our findings indicated that the project can be classified as a partial failure because few of the centres, operating in some are as of the community, offered socio-economic advancement. Our results a lso indicated that the project design reality gap is quite significant . This gap occurred due to poor planning and implementation of the pro ject. Our research reveals several challenges that could impact upon t he successfulness of the project provide a foundation for further rese arch and add to existing literature. The challenges associated with th e project we identify include poor state of power supply, lack of comm unity engagement during the project planning and implementation, lack of commitment from the Local Government Administration. Our research h as potential in adding ICT4D literature, reveals how ICT4D project eva luation can be carried out using design reality gap framework and prov ides guideline for policy makers.